Pengaruh Media Monopoli terhadap Hasil Belajar Siswa Kelas V Tema tentang Keberagaman Budaya Bangsaku di Sekolah Dasar Negeri 105273 Helvetia - Eva Septiany Damanik; Leni Malinda; Nizmi Putri (Medan Resource Center, 2026)
Learning outcomes in elementary education are strongly influenced by the selection of instructional media capable of fostering students' engagement and participation during classroom activities. This study investigates the effect of Monopoly game-based learning media on the learning outcomes of fifth-grade students in the My Nation's Cultural Diversity thematic unit at State Elementary School Number 105273 Helvetia. Employing a quantitative approach with a quasi-experimental design, the research compared students' learning outcomes before and after the implementation of Monopoly-based instructional media. Data were collected through achievement tests and analyzed using appropriate statistical techniques to determine the significance of the observed differences. The findings reveal that the use of Monopoly learning media significantly improved students' learning outcomes by creating a more interactive, enjoyable, and student-centered learning environment while enhancing motivation, collaboration, and conceptual understanding of Indonesia's cultural diversity. These results demonstrate that integrating educational game-based media into thematic instruction contributes positively to students' academic achievement and classroom engagement. The study concludes that Monopoly learning media represents an effective instructional strategy for improving learning outcomes in elementary education, particularly in thematic learning that emphasizes students' active participation and meaningful learning experiences.